The effect of resistant starches on fat oxidation in healthy adults as measured by a 13CO2-breath test - Wutzke, Klaus D.; Schmidek, Kerstin V. (Isotopes in environmental and health studies, 2017)
A resistant starch (RS) mixture (MIX) consisting of fibre of potatoes (FP) and wrinkled pea starch (WPS), and high amylose maize starch (HAMS) were supplemented in adults to evaluate their effects on fat oxidation by means of a 13 CO 2 -breath test. Sixteen subjects received a regular diet either without or with the supplementation of MIX and HAMS in randomised order. After administration of a [U- 13 C]algal lipid mixture, exhaled air was collected over 14 h in 0.5- and 1-h intervals. The 13 C abundances were measured by nondispersive infrared spectroscopy. In comparison to the dry run (DR), supplementation with MIX and with HAMS increased the cumulative percentage dose recovery: (DR: 16.7 %, MIX: 16.9 %, HAMS: 18.0 %), but without statistical significance. The colonic degradation of MIX and HAMS to short-chain fatty acids tends to lower the formation of carbohydrate-derived acetyl-CoA and contributes to a postprandial lipid oxidation increase by using fat-derived acetyl-CoA as a compensatory fuel source.